A Deterioration of Anemia in Hemoglobin E Disease caused by Cholestatic Hepatitis A - Helena Fabiani; Suzanna Ndraha; Henny Tanadi Tan; Fendra Wician; Mardi Santoso (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTPatients with hemoglobin E disease usually have mild hemolytic anemia and mild splenomegaly. Acute infection including acute inflammatory disease of the liver caused by hepatitis A viral, which attacks patients with previous hemolytic anemia, may result in deterioration of anemia.A 17-year-old female patient was admitted with chief complaint of having jaundiced body and non-specific prodromal symptoms within one week prior to admission. Physical examination revealed jaundiced skin and sclera as well as tenderness in right upper quadrant of the abdomen. Laboratory tests revealed microcytic hypochromic anemia with hemoglobin (Hb) level of 6.3 g/dL, increased reticulocyte count and abnormal morphology of erythrocyteson blood smear. Hemoglobin electrophoresis indicated hemoglobin E disease and serologic tests suggested a positive anti-HAV immunoglobulin M (IgM) with increased level of liver enzymes and functions. Abdominal ultrasound showed hepatosplenomegaly without extra-hepatic cholestasis. The working diagnosis was hepatitis A with intrahepatic cholestasis and hemoglobin E disease. The patient was treated with hepatoprotector and ursodeoxycholic acid. Anemia was not treated specifically. It was assumed that hemolytic anemia was worsened by acute infection of hepatitis A viral. The assumption had been proven to be right since there was improvement of anemia after the acute infection had recovered. Patients with hemoglobin E disease usually have mild anemia; however, in this case, the hemoglobin level decreased significantly due to the acute co-infection. Keywords: hemoglobin E disease, anemia, acute infection, acute hepatitis A infection